Prevalence and implications of depression in type-2 diabetes mellitus: a follow up study - Rajkumar, Amirthalakshmi; S., Lokesh; B., Sivaprakash; Ramachandrappa, Arun kumar (International Journal of Advances in Medicine, 2019)
Background: There are not many longitudinal or prospective studies to determine the association between Diabetes Mellitus (DM) and depression in Indian scenario. Present study was mainly intended to find out the prevalence of depression in diabetic individuals and its impact on diabetes. The aim of the present endeavour was to study the prevalence of depression in diabetic patients, its impact on the clinical course of diabetes and to study the association between clinical courses of depression and diabetes. Methods: It is a prospective analytical study done in MGMCRI. All diabetic patients, aged 30years and above were taken up. Those who screened positive for depression were further assessed using PHQ9 questionnaire and were subjected to antidepression management. From the total number of diabetic patients screened, the prevalence of depression was calculated. Equal number of T2DM patients who screened negative for psychiatric disorders were taken as control. PHQ-9, FBS, PPBS, HbA1c were measured at baseline and repeated at 3rd month of follow-up. Results: In our study the prevalence of depression among diabetic individuals was found to be 15%. The difference in improvement of HbA1c from baseline to follow up was statistically significant when compared between groups having mild, moderate and severe depression, with maximum fall of HbA1c in the group with severe depression. This implies the positive effect of treating depression on glycemic control. Conclusions: This study shows that when diabetes and depression were addressed together it has a positive effect on the glycemic control and the depressive symptoms emphasizing the need for a collaborative management and need for screening diabetes patients for depression for a better care.